Novel genetic alterations in liver cancer distinguish distinct clinical outcomes and combination immunotherapy responses - Wang, Yizhou; Shang, Peipei; Xu, Chang; Dong, Wei; Zhang, Xiaofeng; Xia, Yong; Sui, Chengjun; Yang, Cheng (Frontiers in Pharmacology, 2024)
Introduction: Genomic profiling has revolutionized therapeutic interventions and clinical management of liver cancer. However, pathogenetic mechanisms, molecular determinants of recurrence, and predictive biomarkers for first-line treatment (anti-PD-(L)1 plus bevacizumab) in liver cancer remains incompletely understood. Materials and Methods:Targeted next generation sequencing (a 603-cancer-gene panel) was applied for genomic profiling of 232 hepatocellular carcinoma (HCC) and 22 intrahepatic cholangiocarcinoma (ICC) patients, among which 47 unresectable/metastatic HCC patients underwent anti-PD-1 plus bevacizumab therapies. Results: Genomic landscape exhibited that the most commonly altered genes in HCC were TP53, FAT3, PDE4DIP, KMT2C, FAT1, and MYO18A, while TP53, FAT1, FAT3, PDE4DIP, ROS1, and GALNT11 were frequently altered in ICC; and notably, KRAS (18.18% vs 1.29%) and BAP1 (13.64% vs 1.29%) alterations were significantly more prevalent in ICC. Comparison analysis further demonstrated the distinct clinicopathological/genomic characterizations between Chinese and Western HCC cohorts. Genomic profiling of HCC underlying VI showed that LDLR, MSH2, KDM5D, PDE3A, and FOXO1 were frequently altered in the VIs group, compared to patients without VIs. Compared to right hepatic lobe of HCC patients, left hepatic lobe of HCC patients had the superior OS (median OS: 36.77 months vs unreached, p<0.05), and impressively, NOTCH signaling pathway-related alterations were prevalent among right hepatic lobe of HCC patients. Moreover, altered RB1, NOTCH3, MGA, SYNE1, and ZFHX3, as independent prognostic factors, were markedly correlated with OS of HCC patients. Furthermore, altered LATS1 was abundantly enriched in HCC-recurrent group, and which was independent from clinicopathological features in predicting RFS (median RFS of altered type vs wild-type: 5.57 months vs 22.47 months, p<0.01). Regarding those treated HCC patients, TMB value, altered PTPRZ1, and Cell Cycle-related alterations were identified to be positively associated with objective response rate (ORR), but KMT2D alterations were negatively correlated with ORR. In addition, altered KMT2D and Cell Cycle signaling were significantly associated with reduced and increased time to progression (PFS: progression-free survival), respectively.: Comprehensive genomic profiling deciphered distinct pathogenetic mechanisms, and molecular characterizations underlying VI, location of onset, recurrence, and survival time in liver cancer. Identified novel genetic predictors of response to anti-PD-1 plus bevacizumab in HCC facilitated development of an evidence-based approach to therapy.